A VISUAL ANALYSIS OF STRUCTURAL CLADDING IN THE UNIVERSITY OF LAGOS, AKOKA - Akinde, Dr. Toyin Emmanuel; Odeniyi, Akinkunmi Olatunbosum; Balogun, Temitope Toluwalase; Lawuyi, Funmilayo Dorcas; Elebute, Pita Tireni (jfpublisher, 2025)
University of Lagos (UniLag) is synonymous with the municipality of Akoka. It is Nigeria's most cosmopolitan citadel of higher learning, established in 1962 alongside Universities in Nsukka, Zaria, and Ile-Ife, respectively. Her location in Akoka, which implies primacy in Yoruba philology, can be likened to divine providence or coincidence. Little wonder why the institution pitched itself as “The University of First Choice and the Nation’s Pride